The Characteristics Of Users Derivative Company Towards The Company’s Value - Agustin Ekadjaja, Margarita Ekadjaja, Henny, (Jurnal Akuntansi, 2019)
The use of derivative instruments can be used to control financial risk to be able to drive an increase in company value. The contribution of this study is to seek the relationship between variables that can increase company value, then increasing the value of the company can achieve the company's goal of increasing shareholder prosperity. The population in this study are all companies listed in the Sharia Stock Index on the Indonesia Stock Exchange in 2014-2016. Multiple linear regression analysis is used to test the hypothesis. The result of the test showed that the Return On Asset and firm size variables have a significant positive effect on the firm value of derivative users. While capital expenditure and dividend yield showed that there is no significant effect on firm value and the leverage variable showed a significant negative effect on firm value.